Perancangan Aplikasi Pengelolaan Data Desa Mekarmukti Bandung Barat Berbasis Website - Tubagus Riko Rivanthio; Cahyadi Supyansuri (Darma Abdi Karya, 2022)
Mekarmukti Village is located in West Bandung Regency which has data on the area ranging from data on natural resources, human resources, institutions, facilities, and infrastructure. The data must be appropriately managed so that it becomes useful data both for the community in general or the village party in particular in analyzing the needs of village development. The data must be easily accessible, therefore for ease of data management, it is necessary to create an easily accessible application. So based on these needs, it is required to create an application for website-based data management. With website-based data can be accessed easily via the internet. In conducting research on the design of the Mekarmukti village data management application, the waterfall method was used, which began with requirements, planning, modeling, construction, and finally deployment. The website-based Mekarmukti village data management application can assist the village in analyzing data so as to facilitate the development of Mekarmukti village.